2013
DOI: 10.1063/1.4813516
|View full text |Cite
|
Sign up to set email alerts
|

Study of magnetization reversal in LaCr1−xFexO3 compounds

Abstract: Single phase samples of LaCr1−xFexO3 for x = 0–0.50 were prepared and their magnetic properties were studied to understand the magnetization reversal. Magnetization reversal was observed even for 5 at. % of Fe doping and it persisted up to x = 0.15. Ferromagnetic like behavior with a large coercive field of the order of 0.5 T was observed in the intermediate composition range of x = 0.20–0.40. However, for x = 0.45 and 0.50, magnetization reversal was again observed. Magnetization reversal was studied in detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…the Fe ions behave has paramagnetic, typically for the composition range x=0.05-0.15, which is under the influence of negative internal field created by an AFM ordered Cr ions. The MR observed for x=0.45 and 0.50 of Fe substituted LaCrO 3 samples was due the competition between single ion anisotropy and DM interaction [18]. Thus, existence of Cr-Fe random distribution in bulk LaFeO 3 material, observed to show a complex magnetic behaviour, such as MR and the exchange bias (EB) behaviour.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…the Fe ions behave has paramagnetic, typically for the composition range x=0.05-0.15, which is under the influence of negative internal field created by an AFM ordered Cr ions. The MR observed for x=0.45 and 0.50 of Fe substituted LaCrO 3 samples was due the competition between single ion anisotropy and DM interaction [18]. Thus, existence of Cr-Fe random distribution in bulk LaFeO 3 material, observed to show a complex magnetic behaviour, such as MR and the exchange bias (EB) behaviour.…”
Section: Introductionmentioning
confidence: 89%
“…Besides of these reports with anomalous magnetic property of Cr substituted LaFeO 3 was studied for bulk system [16][17][18]. The magnetic and electrical properties can be tuned by wet chemical synthesis and its thermal heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of Nd by La is reported to increase T N value but reduce T SRT [11]. Troyanchuk et al [12] have reported magnetization reversal in NdMn 0.15 Cr 0.85 O 3 compound below 150 K. Even though, there are several reports on the study of sign reversal of magnetization in LaCrO 3 -based system by carrying out substitutions either at La site or at Cr sit [2][3][4] but such reports on NdCrO 3 system is limited. Since NdCrO 3 contains the magnetic rare earth element, it would be interesting to study the transition element substitution at Cr site in order to easily tune the canted ferromagnetic component and investigate the exotic magnetization reversal phenomenon.…”
Section: Introductionmentioning
confidence: 93%
“…Magnetization reversal has been reported in different types of compounds: Sr 2 YbRuO 6 [1], orthochromites [2][3][4], orthovanadates [5,6], intermetallic compounds [7,8], perovskite manganite [9], etc. It is interpreted by considering various mechanisms involving core-shell model, structural transition, ferrimagnetic ordering, ferromagnetic clustering effect, paramagnetic moment under the negative internal field, and the competition between Dzyaloshinsky-Moriya interaction and single-ion anisotropy [4].…”
Section: Introductionmentioning
confidence: 99%
“…In La 0.8 Ce 0.2 CrO 3 , magnetization reversal was interpreted in terms of a core-shell model [10]. The competition between single ion anisotropy and Dzyaloshinky-Moriya (DM) antisymmetric exchange interaction, and the paramagnetic moment of dopant ions in the internal field were used to explain the magnetization reversal of rare earth chromites [11,12]. In La 1 À x Pr x CrO 3 , the magnetization reversal was explained by the antiparallel coupling between doping ion R 3 þ and Cr 3 þ ions [13,14].…”
Section: Introductionmentioning
confidence: 99%